Application of GIS for evaluation of ethnic fault lines of Karachi - Khan, Imran; Hamza, Salma; Burke, Farkhunda; ul-Huda, Syed Nawaz (Penerbit Universiti Kebangsaan Malaysia, 2020)
Karachi, megapolis has witnessed numerous massive homicide incidents waves through the ages. More than ten thousand persons were murdered during 2009-2017. Being a largest cosmopolitan and commercial city of Pakistan, Karachi has a variety of ethnic groups clustered into a highly variegated number of ethnic political groups who on the slightest pretext entangle clashes and head on collisions. Homicide, a primeval crime has been constantly increasing globally with varying spatio-temporal fluctuations depending on level of development of countries, which influences the socio-cultural and political environments of societies. There are various studies on crimes in Karachi but none of them have evaluated their ethnic jolts line with reference of geo-demography. The study is aimed to facilitate concerned authorities, policy makers and scholars towards designing crime elimination guidelines and policies for the most politically, economically and socially strategic hub of the country. Data limitations were experienced during the work although ground truthing with the help of GPS was conducted for location of homicide hotspots and IDW techniques were employed for accuracy of spatial analysis. The result has identified the heart of the city as the most sensitive homicide zone, though 2017 revealed substantial decrease due to the operation initiated in September 2014 by newly elected federal govt. The lucrativeness of Karachi, has favored it as a haven Routine Activity Theory with fluctuating volumes of homicides concentrate and trajectories through 2009 until 2017. The trajectories being guided by social, ethnicity, magnified by ignorance of the minimal existent socioeconomic policies through official guardian, manifested along the ethnic fault lines.